PELATIHAN LARI-LOMPAT RINTANGAN LEBIH BAIK DARIPADA PELATIHAN LARI-LOMPAT KE DEPAN DALAM MENINGKATKAN HASIL LOMPAT JAUH PADA SISWA SMAN-2 MENGWI BADUNG - raka, I Made; juliasih, Ni ketut ayu (Sport and Fitness Journal, 2015)
This study aimed to determine the training method to improving long jump results of two training methods. Research conducted on 24 students of SMAN-2 Mengwi Badung and divided by into two groups. One group was given run-jump obstacle training and two groups was given run-jump ahead training. The data obtained were analyzed by paired ttest to determine the difference between before and after training in both groups and independent t-test to test the difference in long jump results between groups after training. The results of statistical test, an increase in the long jump results between before and after training in group-1 of 441.67 ± 34.40 cm to 507.50 ± 34.08 cm with a value of p < 0.05 (significantly different) and on -second group increased from 444.58 ± 31.58 cm to 478.33 ± 32.64 cm with a value of p <0.05 (significantly different). Long jump results after training showed significant difference is p <0.05. Thus, training to run-jump the obstacle and run-jump the ahead will increase the long jump results. Run-jump obstacle training more effective than run-jump ahead training to increasing the long jump results. For that is expected to coach and gym teacher who trains the long jump branches to apply to runjump obstacle training in providing training.
Keywords: run-jump obstacle training, run-jump ahead training, long jump results